2009
DOI: 10.1373/clinchem.2009.126847
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Plasma B-Type Natriuretic Peptide in the First Days of Life

Abstract: commercial device. This disadvantage is partially offset by the fact that our gels can accommodate 80 samples per run (compared with 34 for the FlashGel device). Furthermore, our method is markedly less expensive than the FlashGel device with respect to both the apparatus (613 vs 991 euros) and the agarose gels (0.08 vs 0.37 euros; cost per sample for electrophoresis on a 22-g/L NuSieve® agarose gel from Lonza Rockland).Our apparatus is currently being used for various applications, including checking the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 5 publications
3
28
0
Order By: Relevance
“…A possible contributor of post-surgical BNP drop in the neonatal age group may be represented by physiological changes of BNP that are much more pronounced in the first days of life but tend to progressively decrease during the first month of life. 26, 27 Maturational decrease of BNP, however, is linear while post-surgical neonatal BNP quickly drops. Furthermore, major postnatal variations in BNP generally occur within the first 4 days of life; 27 but in the present study surgical treatment was done only in a negligible number of babies (n=5), in that time period.…”
Section: Discussionmentioning
confidence: 99%
“…A possible contributor of post-surgical BNP drop in the neonatal age group may be represented by physiological changes of BNP that are much more pronounced in the first days of life but tend to progressively decrease during the first month of life. 26, 27 Maturational decrease of BNP, however, is linear while post-surgical neonatal BNP quickly drops. Furthermore, major postnatal variations in BNP generally occur within the first 4 days of life; 27 but in the present study surgical treatment was done only in a negligible number of babies (n=5), in that time period.…”
Section: Discussionmentioning
confidence: 99%
“…high in the first few days of life, then hormone circulating levels fall rapidly and progressively over the next 2 weeks, and finally reach a plateau with stable levels up to the onset of puberty (2). On the other hand, some studies from our laboratory demonstrated that time courses of BNP levels can also affect diagnostic accuracy of BNP assay in the first weeks of life (4).…”
mentioning
confidence: 87%
“…A total of 436 healthy control subjects, including 234 neonates (median age, 3 d [2][3][4][5][6][7][8]) and 202 older children (median age, 24 mo ), were also enrolled as a control group and to determine normal reference values. A total of 436 healthy control subjects, including 234 neonates (median age, 3 d [2][3][4][5][6][7][8]) and 202 older children (median age, 24 mo ), were also enrolled as a control group and to determine normal reference values.…”
Section: Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations